Interleukin-18 cytokine gene polymorphism 137G/C (rs187238) and susceptibility to tuberculosis in north India - Karan Gupta; Vibha Uppal; Pranav Ish; Shubham Singh Chauhan; Sibasish Patro; Neeraj Kumar Gupta (Monaldi Archives for Chest Disease)
Tuberculosis (TB) regained its position globally as the leading cause of mortality from a single infectious agent after being surpassed by COVID-19 for 3 years consecutively. Host genetic factors, particularly cytokine gene polymorphisms, play a significant role in influencing susceptibility to TB. Interleukin-18 (IL-18) is a proinflammatory cytokine involved in immune regulation against Mycobacterium tuberculosis. This study aimed to evaluate the association of IL-18 gene polymorphism (rs187238) with susceptibility to TB and its effect on serum IL-18 levels in a north Indian population. A case-control study was conducted with 100 newly diagnosed TB patients (pulmonary and extrapulmonary) and 100 age- and gender-matched healthy controls. Serum IL-18 levels were measured using sandwich enzyme-linked immunosorbent assay, and the IL-18 gene polymorphism at rs187238 was analyzed by polymerase chain reaction-restriction fragment length polymorphism. The association between IL-18 polymorphism, TB susceptibility, and serum IL-18 levels was statistically evaluated. Mean serum IL-18 levels were significantly elevated in TB patients (400.42±149.58 pg/mL) compared to controls (96.05±40.67 pg/mL; p<0.01). The distribution of IL-18 genotypes showed that individuals with GC/CC genotypes had a significantly lower risk of developing TB compared to the GG genotype [odds ratio (OR)=0.31; 95% confidence interval (CI)=0.20-0.88; p=0.0167]. Additionally, the C allele conferred a protective effect against TB (OR=0.33; 95% CI=0.22-0.51; p<0.0001). Serum IL-18 concentrations varied significantly with genotype, with the highest levels observed in CC genotype carriers in both cases and controls (p<0.01). Thus, our study suggests that IL-18 polymorphism at rs187238 significantly influences susceptibility to TB in the north Indian population. The C allele and GC/CC genotypes appear to confer a protective effect, possibly through modulation of IL-18 serum levels. IL-18 rs187238 polymorphism may serve as an independent predictive marker for TB risk, though larger studies are recommended for validation.